Evidence-Informed Educational Practice in Catalan Education: From Public Agenda to Teachers’ Practice - Georgeta Ion; Cecilia Inés Suárez; Anna Diaz Vicario (Center for Educational Policy Studies Journal)
Catalonia has a long tradition of school innovation movements. These have increased in recent years as public administration and private entities have initiated substantial school reforms oriented toward the use of evidence in teaching practice. As the Catalan education system is highly autonomous, not all schools have embraced the evidence-informed practice (EIP) movement, and this has created differences between schools that choose to implement a change or innovation based on scientifically demonstrated evidence and those that do not. In the present paper, we will attempt to understand the current state of the inclusion of evidence-informed practice in Catalonia and to assess teachers’ perceptions of its adoption as part of their daily practice. In order to address these issues, we start by exploring the legal and structural framework grounding the implementation of evidence-informed practice in the Catalan system, and through interviews conducted in a sample of primary school leaders and teachers, we approach the organisational and individual level to explore the opportunities to implement an authentic evidence-informed practice approach in the Catalan education system.